Content management systems : an introduction / Mohamad Noorman Masrek - Masrek, Mohamad Noorman (Faculty of Information Management, 2005)
With the explosive growth of the Internet, fundamental content management needs have also grown. No longer can information be published online in a manual process and be left unattended. A content management system (CMS) represents a revolutionary way to manage online content when compared to traditional methods. A CMS is the tool that allows us to collect, manage and publish information to a variety of medium in an efficient, timely, and duplicable manner. CMS can be categorized into File-Based Content Management for Sharing, Web-Site Content Management for Publishing and Enterprise-wide Content Management for Integration and Publishing. The functionalities of a generic CMS can be broken into Content Collection or Authoring, Workflow, Storage or Management and Publishing. The need for a CMS can be gauged by the huge amount of content, the enormous amount of change in the content, and the massive number of publications to create. The use of CMS promises many advantages in the form of empowering content, decrease cost, increase revenue, improve accountability, and maintain consistency.